An ethnography of NGO practice in India : utopias of development - Allen, Stewart (New ethnographies., 2018)
"Through an ethnographic study of the 'Barefoot College', an internationally renowned non-governmental development organisation (NGO) situated in Rajasthan, India, this book investigates the methods and practices by which a development organisation materialises and manages a construction of success"--Electronic resource home page, viewed March 23, 2020